Treatment of Diesel Oil Contaminated Soil by Ex-situ Bioremediation - Rajamohan, N.; Manivasagan, R.; Al Fazari, F. (Engineering, Technology & Applied Science Research, 2019)
Treatment of oil-polluted soil is a challenging problem faced by all refineries and petrochemical industries. In this research study, bioremediation of diesel oil contaminated soil was conducted for diesel concentration ranging from 5% to 20%. The physicochemical characteristics of diesel oil contaminated soil were studied. The effects of soil amendments, namely coconut ash powder, biofilter activated sludge, and NPK fertilizer, on total petroleum hydrocarbon removal efficiency were studied. The maximum total petroleum hydrocarbon removal efficiency achieved was 94.5% when 4g NPK, 40g of activated sludge and 40g of coconut ash powder per 1000g of contaminated soil were used. The studies on the effect of temperature confirmed the optimal temperature as 35°C. The parametric studies confirmed that the degradation efficiency decreased with increase in diesel oil concentration.